Marine Niche: Applications in Pharmaceutical Sciences 2020
DOI: 10.1007/978-981-15-5017-1_11
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed and Sea Anemones Proteins as a Source of New Pharmaceutical Active Principles

Abstract: Among marine sources, seaweeds and sea anemones are highly attractive for their diversity and complex composition, the major components being polysaccharides, proteins, pigments, phenolic compounds, vitamins and minerals. Seaweeds and sea anemones could be a source of different proteins and peptides with unique structures with interesting biological properties, such as antitumoral, antimicrobial, antiinflammatory, antidiabetic, antioxidant, among others. This chapter presents an overview on the marine algal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Seaweeds contain several bioactive compounds, including polysaccharides, polyphenols, lipids, polyunsaturated fatty acids (PUFAs), sterols, proteins, dietary fiber, pigments, and vitamins [101,102]. Several studies have revealed that the seaweeds are an excellent source of various proteins (amino acids, peptides, phycobiliproteins, and lectins) with interesting biological properties, such as antihypertensive, antioxidant, antidiabetic, anti-inflammatory, antitumoral, antiviral, and antimicrobial [20,32,103]. Table 6 summarizes the bioactive compounds and their functional properties for selected seaweeds.…”
Section: Functional Properties Of Seaweed Proteins and Their Role In ...mentioning
confidence: 99%
“…Seaweeds contain several bioactive compounds, including polysaccharides, polyphenols, lipids, polyunsaturated fatty acids (PUFAs), sterols, proteins, dietary fiber, pigments, and vitamins [101,102]. Several studies have revealed that the seaweeds are an excellent source of various proteins (amino acids, peptides, phycobiliproteins, and lectins) with interesting biological properties, such as antihypertensive, antioxidant, antidiabetic, anti-inflammatory, antitumoral, antiviral, and antimicrobial [20,32,103]. Table 6 summarizes the bioactive compounds and their functional properties for selected seaweeds.…”
Section: Functional Properties Of Seaweed Proteins and Their Role In ...mentioning
confidence: 99%